2004
DOI: 10.1111/j.1464-410x.2004.05177.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion properties of transurethral intraprostatic injection

Abstract: OBJECTIVES To evaluate the location and extent of diffusion that occurs when liquid is injected transurethrally into the prostate gland, by correlating real‐time fluoroscopy and gross pathology, and to quantify the variables that influence intraprostatic diffusion during chemoablation of the prostate. MATERIALS AND METHODS A solution of diatrizoate meglumine (HypaqueTM, Nycomed, Princeton, NJ) gentamicin and methylene‐blue dye (HGM) was injected transurethrally into the prostate in six dogs, using a passive‐de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…There is a correlation between the volume injected and the size of the lesion when using a standard 21-G needle. 9 Further studies are needed to elucidate the correlation between the injected dose and the volume of tissue in which the drug is distributed using CED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a correlation between the volume injected and the size of the lesion when using a standard 21-G needle. 9 Further studies are needed to elucidate the correlation between the injected dose and the volume of tissue in which the drug is distributed using CED.…”
Section: Discussionmentioning
confidence: 99%
“…Results from this study showed the variability is likely owing to various degrees of ethanol backflow along the needle tract. 8,9 We hypothesized that the variability is secondary to the tissue type the needle tip is imbedded into, causing differences in resistance and diffusion during injection. As a possible solution, we investigated convection enhanced delivery (CED) using a microporous hollow fiber catheter (MiHFC).…”
Section: Introductionmentioning
confidence: 99%
“…A disadvantage with liquid alcohol is that its distribution is difficult to control, making accurate placement problematic [24]. Larson et al [25] tried to overcome this problem by using anhydrous ethanol in gel form.…”
Section: Ethanolmentioning
confidence: 99%
“…We previously reported that the prostate capsule acts as a barrier that prevents the injected substance from diffusing beyond the organ, making it a suitable target for drug delivery using direct intraprostatic injection. 2,3 …”
mentioning
confidence: 99%
“…Variable clinical outcomes were also reported, 5–8 likely due to varying resistance of the tissue type in which the needle tip was embedded (stroma, muscle or glandular tissue) as well as backflow of the substance along the needle tract. 3 …”
mentioning
confidence: 99%